Методичні вказівки для самостійної роботи з курсу "Економіка програмного забезпечення" - Вовк, Марина Анатоліївна; Чередніченко, Ольга Юріївна; Орловський, Дмитро Леонідович; Копп, Андрій Михайлович (НТУ "ХПІ", 2017)
These guidelines were designed for independent work on the course of "Software Economics". It is especially useful for students, who is studding in English and foreign students. The objectives are to provide an empirical view of where the effort and money goes when we build large software systems and to suggest ways of reducing and controlling software costs.
Guidelines for independent work on the course "Software economics"
Keywords: software economics; software engineering; software cost estimation methods; COCOMO model; function point analysis; PERT model; економіка програмного забезпечення; інженерія програмного забезпечення; програмне забезпечення; методи оцінки вартості ПЗ